2017
DOI: 10.1111/are.13514
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of the winged pearl oyster Pteria sterna (Gould, 1851) in suspended culture in the tropical Eastern Pacific: Influence of environmental factors

Abstract: The growth, survival and influence of environmental factors were analysed in two cohorts of cultured Pteria sterna in Ayangue Bay, Province of Santa Elena, Ecuador (tropical Eastern Pacific). Juveniles representing cohorts I and II (8.4 AE 0.54 and 5.0 AE 0.17 mm in dorso-ventral axis) were deployed in November 2015 and Februwileyonlinelibrary.com/journal/are Aquaculture Research. 2018;49:832-838.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
1
16
0
4
Order By: Relevance
“…In spite of the environmental variability observed, particularly in salinity, the continuous growth and the total survival of the organisms suggest that they were physiologically unstressed, corroborating the observation of Lodeiros et al () of high resilience and adaptability of the species to environmental variability. In this way, P. sterna is not only capable of adapting to large variations of intraday temperatures, up to 6°C (Lodeiros et al, ), but of resisting elevated temperatures (26–27°C) with high growth rates. In addition to the adaptability to temperature variability and elevated temperatures, our results support adaptability to salinity, at least up to the 12 UPS registered at the end of the study period.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…In spite of the environmental variability observed, particularly in salinity, the continuous growth and the total survival of the organisms suggest that they were physiologically unstressed, corroborating the observation of Lodeiros et al () of high resilience and adaptability of the species to environmental variability. In this way, P. sterna is not only capable of adapting to large variations of intraday temperatures, up to 6°C (Lodeiros et al, ), but of resisting elevated temperatures (26–27°C) with high growth rates. In addition to the adaptability to temperature variability and elevated temperatures, our results support adaptability to salinity, at least up to the 12 UPS registered at the end of the study period.…”
supporting
confidence: 85%
“…Its geographic distribution is from Morro Santo Domingo, in Baja California (28.2° N), to Ancon, Lima, Peru (11.8 S) (Coan & Valentich, ), encompassing also all American pacific tropical region. In equatorial coastal areas, Jara, Gregori, and Freites () and Lodeiros et al () showed a high growth rate, where the species is not significantly affected by the variability of environmental factors and can reach about 100 mm in length during 1 year of cultivation. This makes P. sterna an emerging species for aquaculture in tropical areas of the American Pacific Ocean, and studies should be performed aimed at optimising the culture techniques.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The culture of Pteria sterna is based on spat collected from the wild (Lodeiros et al., 2018; Treviño et al., 2019), but recruitment in Mexico shows more and more variations that put in risk the amounts of juveniles needed for suitable operations (Gómez‐Robles, Mazón‐Suástegui, Acosta‐Salmón, Hawkyns‐Martínez, & Saucedo, 2013). The solution is to produce the spat in hatcheries as it occurs for various bivalve species in different countries (Helm, Bourne, & Lovatelli, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both farms have been operating for more than 20 years, and their production is based on mabes and nucleus implants to produce pearls. These are the only companies in the world that produce this type of gems from P. sterna since the species produces an iridescent nacre suitable for quality pearls (Lodeiros et al., 2018; Treviño, Vélez‐Falcones, & Lodeiros, 2019).…”
Section: Introductionmentioning
confidence: 99%